Training on creating student worksheets (LKPD) based on problem-based learning within the kurikulum merdeka - Isna Rahmawati; Putri Zudhah Ferryka; Nela Rofisian; Sri Suwartini (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service in the form of training in making LKPD based on problem-based learning aims to introduce and assist in its implementation within the merdeka curriculum, enabling its application in elementary schools. Problem-based learning, also known as LKPD, can be applied in elementary schools across all subjects. Learning activities with LKPD based on problem-based learning become more structured and meaningful for students. The participants of this community service consisted of the principal, teachers, and students who were carrying out field experience practice at SD N 2 Prambanan, Klaten. The method used in this training is participatory action research (PAR), consisting of material delivery, mentoring, and discussion activities. The material provided in this training is the delivery of theory (definition, characteristics, and syntax of problem-based learning), practice in compiling LKPD based on problem-based learning, and evaluation. The results of this community service activity demonstrate success in mastering the creation of LKPD through participant training. This can be seen from the high enthusiasm in every stage of the training implementation.